Physics of semiconductors and their heterostructures - Singh, Jasprit (New York, NY : McGraw Hill Education, 1993)
This graduate-level textbook offers a comprehensive treatment of the underlying physics behind modern semiconductor devices, with applications to specific modern solid-state devices throughout. Modular in organization, it should be suitable for a range of courses in solid state physics and devices in both physics and electrical engineering departments.
Preface -- Introduction -- 1. The Free Electron Picture -- 2. Periodicity: Crystal Structures -- 3. Wave Diffraction in Periodic Structures -- 4. Electrons in Periodic Structures -- 5. Semiconductor Bandstructure -- 6. Bandstructure Modifications: Alloys and Heterostructures -- 7. Bandstructure Modifications Through Strain -- 8. Doping of Semiconductors -- 9. Lattice Vibrations: Phonons -- 10. Transport: General Formalism -- 11. Defect and Carrier-Carrier Scattering -- 12. Phonon Scattering -- 13. The Velocity-Field Relations -- 14. Transport in Heterosstructures -- 15. Interactions of Photons with Semiconductors -- 16. Optical Properties in Semiconductors: Excitonic Transitions -- 17. Semiconductors in Magnetic Fields -- 18. Defects and Disorder in Semiconductors -- 19. And Now Something of Real Consequence: Devices -- Appendixes -- Index.
Includes bibliographical references and index.
Keywords: SEMICONDUCTORS